2018
DOI: 10.1097/ccm.0000000000003147
|View full text |Cite
|
Sign up to set email alerts
|

Early Evidence of Sepsis-Associated Hyperperfusion—A Study of Cerebral Blood Flow Measured With MRI Arterial Spin Labeling in Critically Ill Septic Patients and Control Subjects*

Abstract: In septic patients, cerebral blood flow was higher than in sedated control subjects and did not vary with mean arterial pressure targets. Further research is required to understand the clinical significance of cerebral hyperperfusion in septic patients on vasopressors and to reassess the neurologic effects of current mean arterial pressure targets in sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…32 In contrast, a recent pilot study using arterial spin labeling magnetic resonance imaging demonstrated increased cerebral blood flow in patients with delirium compared to controls. 27 Clearly, the alterations in cerebral blood flow and perfusion during delirium warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…32 In contrast, a recent pilot study using arterial spin labeling magnetic resonance imaging demonstrated increased cerebral blood flow in patients with delirium compared to controls. 27 Clearly, the alterations in cerebral blood flow and perfusion during delirium warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to demonstrate compromised NVC responses in a relevant preclinical animal model of geriatric sepsis. Previous clinical studies reported multifaceted effects of sepsis on cerebral blood flow regulation (Terborg et al, 2001;Bowie et al, 2003;Pfister et al, 2008;Toksvang et al, 2014;Vasko et al, 2014;de Azevedo et al, 2017;Crippa et al, 2018;Masse et al, 2018). The emerging concept is that both reduced cerebral blood flow and altered autoregulation contribute to sepsis-associated encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral blood flow (CBF) autoregulation can maintain consistent CBF within a certain blood pressure range, and patients with sepsis usually have damaged CBF autoregulation[ 22 ]. Masse et al [ 23 ] showed that CBF in sedated septic patients was 62% higher than that in control subjects and did not change with mean arterial pressure. The relationship between inflammation and cerebral hyperperfusion needs to be further studied[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Masse et al [ 23 ] showed that CBF in sedated septic patients was 62% higher than that in control subjects and did not change with mean arterial pressure. The relationship between inflammation and cerebral hyperperfusion needs to be further studied[ 23 ].…”
Section: Discussionmentioning
confidence: 99%